Anti-CXCR4 Single-Chain Variable Fragment Antibodies Have Anti-Tumor Activity - Liang, Guang-Quan; Liu, Jing; Zhou, Xiao-Xin; Lin, Ze-Xiong; Chen, Tao; Chen, Guo; Wei, Henry (Frontiers in Oncology, 2020)
Monoclonal antibodies (mAbs) are large and have limitations as cancer therapeutics. Human single-chain variable fragment (scFv) is a small antibody as a good alternative. It can easily enter cancer tissues, has no immunogenicity and can be produced in bacteria to decrease the cost. The chemokine receptor CXCR4 is overexpressed in different cancer cells. It plays an important role in tumor growth and metastasis. Its overexpression is associated with poor prognosis in cancer patients and is regarded as an attractive target for cancer treatment. In this study, a peptide on the CXCR4 extracellular loop 2 (ECL2) was used as an antigen for screening a human scFv antibody library by yeast two-hybrid method. Three anti-CXCR4 scFv antibodies were isolated. They could bind to CXCR4 protein and three cancer cell lines (DU145, PC3 and MDA-MB-231) and not to 293T and 3T3 cells as negative controls. These three scFvs could decrease the proliferation, migration and invasion of these cancer cells and promote their apoptosis. The two scFvs were further examined in a mouse xenograft model, and they inhibited the tumor growth. Tumor immunohistochemistry also demonstrated that the two scFvs decreased cancer cell proliferation and tumor angiogenesis and increased their apoptosis. These results show that these anti-CXCR4 scFvs can decrease cancer cell proliferation and inhibit tumor growth in mice, and may provide therapy for various cancers.